An Online Course in Optics (Physics III) at UPIITA I.P.N. in Blackboard Computing Platform - Aburto, A.; Espinoza, N. (Revista Cubana de Física, 2007)
We present an elementary course of Optics for engineers, where we use the Informatics Platform Blackboard, this course is an educational research, and it is registered in our institute. This is the consequence of the Basic course of Electricity and Magnetism of the Curriculum of Telematic, Mecatronic and Bionic Engineering of the Unidad Interdisciplinaria en Ingenieria y Tecnologias Avanzadas of Instituto Politecnico Nacional. The foundation materials in this project are: i) One Text captured in Word, covering basic knowledge in Classic Electricity and Magnetism needed in Optics. ii) A set of simulation of Java Applets and Flash Animations, for the refinement of knowledge. iii) The exposition of the course with a set of Power Point Presentation. We are imposing an initial exam of basic knowledge of students. Emphasis is done in development of Polarized formulation of Monochromatic Waves in Jones Linear Algebra, complex index of refraction, and their relation with complex Wave Vectors.